Drying grapes under controlled conditions with the aim of producing prošek, traditional Dalmatian sweet wine - Ivana Tomaz; Nina Buljević; Karla Gulan; Iva Šikuten; Darko Preiner; Jelena Gulan; Ante Gospić; Edi Maletić (Journal of Central European Agriculture, 2025)
Prošek, a traditional dessert wine, is made from overripe, dried grapes grown in Coastal Croatia. The characteristic of prošek is the production from grapes that are partially dried on the vine or after harvest, which allows for an increase in the concentration of total soluble solids and other compounds found in the must. This research aimed to determine the phenolic composition of grapes from grapevine varieties Plavac mali and Plavina, which were dried in two ways, under conventional conditions in a greenhouse and under controlled conditions in a drying room. The analysis of polyphenolic compounds was performed using high-performance liquid chromatography. The results showed that the levels of total flavonol glycosides, phenolic acids, stilbenes, and flavonols increased in both treatments, and in the case of total anthocyanins, the concentration increased in the greenhouse, while it decreased in the drying room.